Verification of greenhouse gas emission reductions: the prospect of atmospheric monitoring in polluted areas - Levin, Ingeborg; Hammer, Samuel; Eichelmann, Elke; Vogel, Felix R. (Philosophical transactions of the Royal Society. A, Mathematical, physical and engineering sciences, 2011)
Independent verification of greenhouse gas emissions reporting is a legal requirement of the Kyoto Protocol, which has not yet been fully accomplished. Here, we show that dedicated long-term atmospheric measurements of greenhouse gases, such as carbon dioxide (CO2) and methane (CH4), continuously conducted at polluted sites can provide the necessary tool for this undertaking. From our measurements at the semi-polluted Heidelberg site in the upper Rhine Valley, we find that in the catchment area CH4 emissions decreased on average by 32±6% from the second half of the 1990s until the first half of the 2000s, but the observed long-term trend of emissions is considerably smaller than that previously reported for southwest Germany. In contrast, regional fossil fuel CO2 levels, estimated from high-precision 14CO2 observations, do not show any significant decreasing trend since 1986, in agreement with the reported emissions for this region. In order to provide accurate verification, these regional measurements would best be accompanied by adequate atmospheric transport modelling as required to precisely determine the relevant catchment area of the measurements. Furthermore, reliable reconciliation of reported emissions will only be possible if these are known at high spatial resolution in the catchment area of the observations. This information should principally be available in all countries that regularly report their greenhouse gas emissions to the United Nations Framework Convention on Climate Change.